Efficacy of ethyl alcohol and quaternary ammonium in hospital medical equipment disinfection - Adriana Sierra Assencio Almeida Barbosa; Gleice dos Santos Carneiro; Larissa Fernandez Repullio; Mônica da Silveira; Sônia Maria Usó Ruiz Silva; Fátima Regina Vilani-Moreno (Universidade de Santa Cruz do Sul, 2018)
Background and Objectives: Hospital environments may harbor pathogenic and opportunistic microorganisms, and the cleaning and disinfection process is important for the control of Health Care Related Infections (IRAS). Thus, the objective of this work to evaluate compare the efficacy of ethyl alcohol and quaternary ammonium in the disinfection of hospital medical equipment against Staphylococcus aureus (S. aureus). Methods: decontamination of 10 hospital medical equipment contaminated with a suspension of S. aureus ATCC 25923. The decontamination occurred with ethyl alcohol at concentrations of 46.2%, 70% and 99% and with the quaternary ammonium of 1st generation and 5th generation. After the decontamination, samples were harvested from the surface of the equipment for bacterial culture. Results: bacterial growth was verified in 80% of the equipment decontaminated with alcohol 46.2% and 99%. There was no bacterial growth on the surface of equipment decontaminated with alcohol 70% and quaternary ammonium. Conclusion: the disinfection processes with alcohol 70% and quaternary ammonium 1st and 5th generation were effective in the control of S. aureus, proving the effectiveness of these products in the disinfection of hospital medical equipment.